T4 squamous cell cancer of buccal mucosa successfully treated combination of interstitial brachytherapy, concurrent chemo-radiotherapy and salvage surgery - Sharma, Jyoti; Sharma, Aman; Verma, Swati (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
We report a case of advanced case of right sided buccal mucosa deemed inoperable achieving long term cure with a combination of interstitial brachytherapy and concurrent chemoradiotherapy (CRT) followed by salvage surgery for small recurrence. The patients were considered for upfront double plane 12 catheter implant to a dose of 25 Gy in 8 fractions at the rate of 3.125 Gy per fraction. Two fractions were delivered in a day at least 6 hours apart. Thereafter patient was subjected to CRT to a dose of 40 Gy in 20 fractions. At follow up there was complete resolution of disease barring a small induration raw area at angle of mouth, which was successfully managed by salvage surgery. Patient is now on regular follow up for 18 months from completion of treatment and is disease free for 1 year.